PENGARUH MODEL GDL DISERTAI FEEDBACK TERHADAP HASIL BELAJAR SISWA SMA PADA MATERI HIDROLISIS GARAM - Umarela, Septiawan Hady; Hairida, Hairida; Harun, A. Ifriany (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research is based on the students who passive and the monotonous teaching with lecture method from teacher during the learning process so that impacts to the achievement. The purpose of this study is to determine the difference of achievement and the influence of the use of guided discovery learning model with feedback on the students's achievement on the salt hydrolysis material. The form of the research used is quasi experiment with the research design